Time Lapse (4d) Seismic Signal Detectability Improvement Using Co-Processing Technique On Carbonate Reservoirs - Mohamed Mahgoub, Mohamed Abdelghany (2023)
4D seismic studies are used to monitor the performance of hydrocarbon reservoirs during production or injection phases. Repeated 3D seismic surveys must be able to measure a 4D signal that can detect fluids substitution or pressure changes that may take place during reservoir production or injection of water or gas over a period of time. In practice, the seismic signal allied with such changes could be perceptible in clastic reservoirs whereas it could be negligible in heterogeneous carbonate reservoirs. Repeating 3D seismic surveys with the same acquisition geometry is usually difficult in the Middle East due to environmental changes (e.g., rough terrain, water currents, seasonal changes, and field production installations). Therefore, three oil and gas fields of offshore Abu Dhabi in the United Arab Emirates with scarce seismic acquisition repeatability have been selected for this study. In this study, the 4D seismic co-processing for the three case studies differs from the input data, whether it starts from the seismic field data or from different pre-processing and deconvolution, or whether it starts after the same deconvolution on base and monitor seismic surveys.